Free‐Space Quantum Key Distribution with Single Photons from Defects in Hexagonal Boron Nitride. Issue 9 (3rd August 2022) - Samaner, Çağlar; Paçal, Serkan; Mutlu, Görkem; Uyanık, Kıvanç; Ateş, Serkan
Abstract: Efficient single photon generation is an important requirement for several practical applications in quantum technologies, including quantum cryptography. A proof‐of‐concept demonstration of free‐space quantum key distribution (QKD) is presented with single photons generated from an isolated defect in hexagonal boron nitride (hBN). The bright source operating at room temperature is integrated into a QKD system based on B92 protocol and a sifted key rate of 238 bps with a quantum bit error rate of 8.95% are achieved at 1 MHz clock rate. The effect of temporal filtering of detected photons on the performance of QKD parameters is also studied. It is believed that these results will stimulate the research on optically active defects in hBN as well as other 2D‐based quantum emitters and their applications within quantum information technologies including practical QKD systems. Abstract : Quantum key distribution (QKD) is one of the most mature applications of single photon sources (SPSs). In this article, an isolated defect in hexagonal boron nitride is used as an efficient room temperature SPS, and its first implementation into a free‐space B92‐based QKD is demonstrated. A security analysis of the system using the measured parameters of the SPS is also discussed.